PENYELESAIAN SENGKETA HAK MEREK DAGANG TERHADAP PENIRUAN MEREK FURNITURE BERDASARKAN UU NO.15 TAHUN 2001 - Chien Ni; Gunardi Lie; Moody Rizqy Syailendra Putra (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2021)
With the variety of product brands offered by businesses to consumers or the public, people are often faced with various choices. Lower middle class people who want to use well-known branded products choose to buy fake and imitation products. With the widespread occurrence of brand counterfeiting in Indonesia, the name and image of the Indonesian state becomes bad because it is considered a violator of Intellectual Property Rights. The regulation of well-known marks in Indonesia is contained in the old Trademark Law, namely Law No. 15 of 2001 contained in article 6 paragraph 1 letter (b) where a mark that has similarities in principle or in its entirety with a well-known mark belongs to the third party. For goods and/or the like, the application for registration of the mark must be rejected by the Directorate General of Intellectual Property Rights. This study uses a descriptive method to find out how to research how to imitate famousbrands in Indonesia. In practice in Indonesia, the implementation of the protection of well-known marks is still experiencing obstacles, for example the knowledge and understanding of law enforcers on well-known brands that still need to be improved. Cases that often occur in the form of imitation of a well-known brand are then imitated. Such as the trademark dispute that occurred in Indonesia between PT. Ratania Equator with IKEA Sweden. Based on the objectives of PT. Ratania Khatulistiwa who filed a lawsuit for the deletion of a registered mark is to be able to use and register the “IKEA” mark which clearly has similarities in principle or in its entirety to the Swedish IKEA brand “IKEA”. even lose public trust.